Marketing for Acceptance - Tina Louise Johnston (Grounded Theory Review: An International Journal)
Becoming a researcher comes with the credentializing pressure to publish articles in peer-reviewed journals (Glaser, 1992; Glaser, 2007; Glaser, 2008). The work intensive process is exacerbated when the author’s research method is grounded theory. This study investigated the concerns of early and experienced grounded theorists to discover how they worked towards publishing research projects that applied grounded theory as a methodology. The result was a grounded theory of marketing for acceptance that provides the reader with insight into ways that classic grounded theorists have published their works. This is followed by a discussion of ideas for normalizing classic grounded theory research methods in our substantive fields.